(untitled) (Jurnal Teknodik, 2022)
This study is a breakthrough in supporting students’ sd, SMP, AND high school in the South Garut in performing information processing of learning both for the exact and social. The study tries to answer the question of how large the focus of information-processing speed of the student learning based on element formation 3dimensi animation on the exact and social subjects (IPS). The study was conducted on students at elementary, junior high, and high school. The study was conducted by using the method of research and development carried out experiments in which this research is considering the second year in which the CAI instructional model and formation animation 3dimensi been designed before. The study was conducted at the elementary school level, junior high, and high school located in the southern Garut, with through stratified random sampling. The results showed that the speed of information processing of learning both exact and social groups (IPS) conducted junior high school students were more superior than the elementary or high school students, through Computer Assisted Instruction teaching model loaded with animation 3dimensi formation.